Immune-Enhancing Effects of Crude Polysaccharides from Korean Ginseng Berries on Spleens of Mice with Cyclophosphamide-Induced Immunosuppression - Nam, Ju Hyun; Choi, JeongUn; Monmai, Chaiwat; Rod-in, Weerawan; Jang, A-yeong; You, SangGuan; Park, Woo Jung (Journal of microbiology and biotechnology, 2022)
C. A. Meyer is well known as traditional herbal medicine, and ginseng berries are known to exhibit potential immune-enhancing functions. However, little is known about the in vivo immunomodulatory activity of Korean ginseng berries. In this study, crude Korean ginseng berries polysaccharides (GBP) were isolated and their immunomodulatory activities were investigated using cyclophosphamide (CY)-induced immunosuppressive BALB/c mice. In CY-treated mice, oral administration of GBP (50-500 mg/kg BW) remarkably increased their spleen sizes and spleen indices and activated NK cell activities. GBP also resulted in the proliferation of splenic lymphocytes (coordinating with ConA: plant mitogen which is known to stimulate T-cell or LPS: endotoxin which binds receptor complex in B cells to promote the secretion of pro-inflammatory cytokines) in a dose-dependent manner. In addition, GBP significantly stimulated mRNA expression levels of immune-associated genes including interleukin-1β ( ), , , , tumor necrosis factor-α ( ), interferon-γ ( ), toll-like receptor 4 ( ), and cyclooxygenase-2 ( ) in CY-treated mice. These results indicate that GBP is involved in immune effects against CY-induced immunosuppression. Thus, GBP could be developed as an immunomodulation agent for medicinal or functional food application.